If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -2 = 3 Reorder the terms: -2 + 3z = 3 Solving -2 + 3z = 3 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3z = 3 + 2 Combine like terms: -2 + 2 = 0 0 + 3z = 3 + 2 3z = 3 + 2 Combine like terms: 3 + 2 = 5 3z = 5 Divide each side by '3'. z = 1.666666667 Simplifying z = 1.666666667
| R/-8=5 | | 3/4t-7/12=1/6 | | -5/9k25 | | Y+5x-3=2y+10x-8 | | 6/7x70 | | 10987-768*4= | | 2+2+4+x+1+4+1+2+x=2x+4x+4 | | -31+11x=9x+15 | | -10n+3(8+8n)=-6(1n-4) | | 20=l(5) | | 2b-4/5=5/3 | | -10+3(8+8n)=-6(1n-4) | | 9-3×5/3=14 | | 2x-4y+10=x+y+20 | | 2+3x=4+6 | | 0.4w+16+4w=27.28 | | X+22=3x-10 | | v=(3)(7)(10) | | 120/(2p)=30 | | 7x+21xy=14 | | 24(x-2)=3(8x+2)-54 | | 3t^2+t-30=0 | | 120/2*p=30 | | 57=n+(n+1) | | 132=4(2x-9) | | f(x)=(1-6t)(3+t) | | 120/2p=130 | | 4n+4=5+3n | | [x+2n(3a+4)]-a= | | -9=3/4m | | 3-(-6+9)-10x=1 | | 4x-8=2(3x-5)+17 |